Implementing the Five-A Model of Technical Refinement: Key Roles of the Sport Psychologist. Issue 4 (1st October 2016) - Carson, Howie J.; Collins, Dave
Abstract : There is increasing evidence for the significant contribution provided by sport psychologists within applied coaching environments. However, this rarely considers their skills/knowledge being applied when refining athletes' already learned and well-established motor skills. Therefore, this article focuses on how a sport psychologist might assist a coach and athlete to implement long-term permanent and pressure proof refinements. It highlights key contributions at each stage of the Five-A model—designed to deliver these important outcomes—providing both psychomotor and psychosocial input to the support delivery. By employing these recommendations, sport psychologists can make multiple positive contributions to completion of this challenging task.